PENGGUNAAN BAHASA GAUL DALAM “MEME” DI MEDIA SOSIAL INSTAGRAM - Muhammad Fajry Anugrah; Azis Azis (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
The Use of Slang in Memes on Social Media Instagram. The study aims to: (1) review the slang form of meme and (2) examine the social function of using slang in meme. This type of study is qualitative work it is done in Makassar and via Internet access to instagram. The research design used is a qualitative description. The focus of the study, which focuses on the slang form of words, phrases, clauses, sentences, and calls, as well as the social function of the slang language, shows a direct view of social media in the slang language. The data-gathering technique covered by the reading and research instrument quotes consists of the main instruments that are researchers and supporting instruments that include smartphones. Studies reveal that the use of slang in social media has been found in two things: (1) expressions of using the slang language, including phrases, clauses, and sentences, and (2) as for the function of using the slang language, four are found: consoling, criticizing, insinuating, and counseling.